Effect of nutritional factors on protease production by isolate pjk 2 2 (1) 2 - Chiu, Li Mei (2014)
Study on the effect of nutritional factors and optimization for maximum protease production was carried out using the isolated bacteria strain PJK 2 2 (1) 2 which collected from Jeli Hot Spring (Kelantan, Malaysia). The bacterium produced protease at maximum rate after 24 hours of incubation at 50°C with agitation speed of 150 rpm and 4% (v/v) starter culture. The best carbon, organic nitrogen and metal ion sources were glucose, tryptone and calcium chloride with protease activity 39.11 U/ml, 39.67 U/ml and 40.78 U/ml respectively. Meanwhile, the addition of inorganic nitrogen source and amino acid reduced the protease production. The combination of glucose, tryptone and calcium chloride produced the maximum protease production was 40.78 U/ml.